Primates of Gashaka Socioecology and Conservation in Nigeria’s Biodiversity Hotspot - Sommer, Volker; Ross, Caroline; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2011)
The remote Gashaka region of north-eastern Nigeria is still largely unexplored. In this premier wilderness, monkeys and apes survive in large numbers – part of a rich assemblage of wildlife at the interface between the dry sub-Saharan Guinea savannah and the moist Cameroonian highlands. Primates include the rarest chimpanzee subspecies, colobus, guenons and baboons, which thrive here despite the wet climate. The main ethnic groups – Fulani cattle herders and Hausa speaking subsistence farmers – still follow age-old traditions. Conservation challenges comprise settlements in protected areas, deforestation, annual fires, livestock grazing and hunting. Primates of Gashaka provides first-hand research accounts in conjunction with the Gashaka Primate Project, founded in 2000. Topics covers primate socioecology; genetics and phylogeography; nutritional ecology; vocal communication and cognition; ethno-botany and ethno-primatology; human subsistence strategies and conflicts with wildlife; as well as habitat surveys assessing success and failure of conservation approaches. The contributions aim for interdisciplinarity and comparative dimensions, across species and the African continent. This pioneering volume about one of the least known iconic primate habitats is of interest to primatologists, anthropologists, policy-makers and conservationists alike.
Foreword -- Conservator General, Nigeria National Park Service -- Contributors -- 1: Exploring and Protecting West Africa’s Primates: The Gashaka Primate Project in Context. Volker Sommer and Caroline Ross -- 2: To Save a Wilderness: Creation and Development of Gashaka Gumti Nationa Park, Nigeria. Richard Barnwell -- 3: Hunters, Fire, Cattle: Conservation Challenges in Eastern Nigeria, with Special Reference to Chimpanzees. Jeremiah Adanu, Andrew Fowler and Volker Sommer -- 4: Monkeys and Apes as Animals and Humans: Ethno-Primatology in Nigeria’s Taraba Region. Gilbert Nyanganji, Andrew Fowler, Aylin McNamara and Volker Sommer -- 5: The Bush as Pharmacy and Supermarket: Mechanisms and Functions of Plant Use by Human and Non-human Primates at Gashaka. Yianna Koutsioni and Volker Sommer -- 6: Fulani of the Highlands: Costs and Benefits of Living in National Park Enclaves. David Bennett and Caroline Ross -- 7: Pan-African Voyagers: Phylogeography of Baboons. Dietmar Zinner, Umaru Buba, Stephen Nash and Christian Roos -- 8: Crop-raiding and Commensalism in Olive Baboons: The Costs and Benefits of Living with Humans. Ymke Warren, James P. Higham, Ann M. MacLarnon and Caroline Ross -- 9: How Different Are Gashaka’s Baboons? Forest and Open Country Populations Compared. Caroline Ross, Ymke Warren, Ann M. MacLarnon and James P. Higham -- 10: Keeping in Contact: Flexibility in Calls of Olive Baboons. Elodie Ey and Julia Fischer -- 11: Not Words but Meanings? Alarm Calling Behaviour in a Forest Guenon. Kate Arnold, Yvonne Pohlner and Klaus Zuberbühler -- 12: Patrirchal Chimpanzees, Matriarchal Bonobos: Potentia Ecological Causes of a Pan Dichotomy. Volker Sommer, Jan Bauer, Andrew Fowler and Sylvia Ortmann -- 13: Panthropology of the Fourth Chimpanzee: A Contribution to Cultural Primatology. Andrew Fowler, Alejandra Pascual-Garrido, Umaru Buba, Sandra Tranquilli, Callistus Akosim, Caspar Schöning and Volker Sommer -- 14: Will the Nigeria-Cameroon Chimpanzee Go Extinct? Models Derived from Intake Rates of Ape Sanctuaries. Nicola Hughes, Norm Rosen, Neil Gretsky and Volker Sommer -- Index.
Keywords: Zoology; Biodiversity; Animal ecology; Applied ecology; Environmental management; Nature conservation; Zoology; Biodiversity; Animal Ecology; Applied Ecology; Environmental Management; Nature Conservation